Principles and applications of photochemistry - Wardle, Brian (Chichester, Wiley, 2009)
A modern introduction to photochemistry covering the principles and applications of this topic from both a physical chemistry and organic chemistry angle. Coverage ranges from subjects such as lasers, the atmosphere, biochemistry, medicine and industry and also includes the latest developments in relation to photochemical molecular machines, photodynamic therapy applied to cancer, photochromatic imaging, and photostabilizers. Little in the way of prior knowledge is assumed, and the reader is aided by numerous worked examples, learning objectives, chapter summaries and problems.
Includes bibliographical references.; Index 241-250p.
Keywords: Photochemistry; Chemistry